Modeling Bauschinger’s Effect in Planar Impact - Partom, Yehuda (European Journal of Applied Sciences, 2022)
Bauschinger’s effect was first noticed as a decrease of yield stress upon unloading from a plastic state in standard tension-compression tests. It was later established that Bauschinger’s effect is a rather general phenomenon in terms of materials and modes of loading. We may say that Bauschinger’s effect may be regarded as a manifestation of anisotropic plasticity caused by the plastic flow itself. Bauschinger’s effect was extensively researched as part of an ongoing effort to understand and model cyclic plasticity. Cyclic plasticity models found in the literature are usually based on concepts of kinematic hardening which are usually rather complex, and they contain many material parameters to be calibrated from tests. Here we’re concerned with modeling Bauschinger’s effect in dynamic situations, specifically in planar impact tests. In such tests Bauschinger’s effect is mainly manifested by the so called quasi-elastic response upon unloading from the shock plateau level. Our approach is based on ideas put forward since the 1930s. First, we show that our model, which we call effective grains model, is able to reproduce the main modes of response in the plastic range, including Bauschinger’s effect. We then apply it to planar impact situations, and show that it’s able to reproduce the so called quasi-elastic response.